Simple approach for the fabrication of PEDOT-coated Si nanowires - Zhu, Mingxuan; Eyraud, Marielle; Rouzo, Judikael Le; Ait Ahmed, Nadia; Boulc’h, Florence; Alfonso, Claude; Knauth, Philippe; Flory, François (Beilstein Journal of Nanotechnology, 2015)
The synthesis of a conformal poly(3,4-ethylenedioxythiophene) (PEDOT) layer on Si nanowires was demonstrated using a pulsed electrodeposition technique. N-type Si nanowire (SiNWs) arrays were synthesized using an electroless metal-assisted chemical etching technique. The dependence of the SiNW reflection on the concentration of the AgNO3 solution was identified. A reflection of less than 2% over the entire visible spectral range was obtained for these structures, evidencing their excellent antireflective properties. The etched SiNWs nanostructures can be further modified by using a tapering technique, which further preserves the strong light trapping effect. P-type PEDOT was grown on these SiNWs using electrochemical methods. Since the polymerization reaction is a very fast process with regards to monomer diffusion along the SiNW, the conformal deposition by classical, fixed potential deposition was not favored. Instead, the core–shell heterojunction structure was finally achieved by a pulsed deposition method. An extremely large shunt resistance was exhibited and determined to be related to the diffusion conditions occurring during polymerization.
Keywords: conductive polymer; core–shell structure; electrodeposition; hybrid material; SiNW